2017
DOI: 10.1002/lio2.60
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Dysfunction and its Association to Chronic Rhinosinusitis: Updated Review

Abstract: Background Poor sleep has significant effects on health contributing to increased morbidity and mortality. The direct and indirect costs of sleep dysfunction total well in to the billions of dollars annually in the US. Chronic rhinosinusitis (CRS) affects up to 16% of the US population and has been linked to poor sleep quality with up to three quarters of patients with CRS reporting poor sleep quality. There is a growing body of literature evaluating the relationship between sleep and CRS. In this review, we o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 83 publications
0
13
0
3
Order By: Relevance
“…La etiología y fisiopatología exacta se desconoce pero alguna teorías señalan que estaría en relación al grado de obstrucción nasal o en el caso de sinusitis crónica, por citoquinas inflamatorias que causan alteraciones en la fase de sueño REM, que en adultos está asociada a consolidación de la memoria (4) . Dentro del sistema inmunitario, los leucocitos producen citoquinas que tienen como función ser mediadores intercelulares y parecen jugar un rol en la regulación inmunitaria y del sueño (6) . Está demostrado que dentro de los estimulantes del sueño están la interleucina (IL), el interferón alfa y el factor de necrosis tumoral-α (TNF-α).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…La etiología y fisiopatología exacta se desconoce pero alguna teorías señalan que estaría en relación al grado de obstrucción nasal o en el caso de sinusitis crónica, por citoquinas inflamatorias que causan alteraciones en la fase de sueño REM, que en adultos está asociada a consolidación de la memoria (4) . Dentro del sistema inmunitario, los leucocitos producen citoquinas que tienen como función ser mediadores intercelulares y parecen jugar un rol en la regulación inmunitaria y del sueño (6) . Está demostrado que dentro de los estimulantes del sueño están la interleucina (IL), el interferón alfa y el factor de necrosis tumoral-α (TNF-α).…”
Section: Discussionunclassified
“…Se ha evaluado un impacto positivo de la septoplastia y la rinoplastia (1) en calidad de sueño, que pareciera estar relacionado al grado de obstrucción nasal previa. Otros estudios respecto a la intervención nasosinusal (operación endoscópica por sinusitis crónica), sugieren que hay un efecto positivo de calidad de sueño expresada por el paciente, pero que parece estar relacionada por el grado de severidad de sinusitis crónica, o ausencia o presencia de pólipos nasales (2)(3)(4)(5)(6) .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Sleep impairment is a common symptom in patients with chronic rhinosinusitis (CRS) [13]. Alt et al reported a 75% prevalence of poor sleep quality in 268 CRS patients, as measured by the Pittsburg Sleep Quality Index instrument [4].…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9] The disease leads not only to a significant health care burden, costing society billions of dollars in direct and indirect costs every year, but also causes a significant quality-of-life (QOL) detriment for affected patients. [10][11][12][13][14] Although sinonasal symptomatology associated with CRS is classically considered to be the primary driver of decreased QOL, 10,15,16 prior work has shown that the ability of CRS to exacerbate other comorbid diseases as well as the frequency of acute exacerbations of CRS (AECRS) are also important drivers of decreased QOL. 11,17,18 AECRS in particular appear to be distinct clinical manifestations of CRS that negatively affect patients, independent of CRS symptomatology.…”
Section: Introductionmentioning
confidence: 99%